2019
DOI: 10.1371/journal.pone.0225540
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of integrative medicine group visits in chronic pain and depressive symptoms: A randomized controlled trial

Abstract: BackgroundCurrent treatment options for chronic pain and depression are largely medication-based, which may cause adverse side effects. Integrative Medical Group Visits (IMGV) combines mindfulness techniques, evidence based integrative medicine, and medical group visits, and is a promising adjunct to medications, especially for diverse underserved patients who have limited access to non-pharmacological therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(77 citation statements)
references
References 87 publications
1
70
0
6
Order By: Relevance
“…The most pronounced degree of beneficial pre–post changes for all evaluated patients was in the PROMIS Pain Interference (PI) and Fatigue domains (mean changes of -3.5 and -3.1, respectively) ( Table 3 ). The mean pain intensity on the Likert scale decreased by 1.0 (from 6.2 to 5.2) (not shown; see also Table 2 for mean changes), similar to the value reported recently for patients with chronic pain and depression who were randomly assigned to participate in integrative medical group visits or primary care provider visits [ 22 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The most pronounced degree of beneficial pre–post changes for all evaluated patients was in the PROMIS Pain Interference (PI) and Fatigue domains (mean changes of -3.5 and -3.1, respectively) ( Table 3 ). The mean pain intensity on the Likert scale decreased by 1.0 (from 6.2 to 5.2) (not shown; see also Table 2 for mean changes), similar to the value reported recently for patients with chronic pain and depression who were randomly assigned to participate in integrative medical group visits or primary care provider visits [ 22 ].…”
Section: Discussionsupporting
confidence: 83%
“…It is possible that potential patients in a control group would improve without any of the nonpharmacological interventions used in our studies as a result of simply being in the group setting and possibly as a result of the placebo effect [ 13 , 36 , 37 ]. It was recently reported in a controlled study [ 22 ] that patients in the control group reported multiple pre–post improvements, with no significant differences between the control (visits with the primary care physician) and the intervention groups (several integrative modalities), except in reducing emergency department visits and pain medication use.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen trials (70%) were for a single LTC, of these: 13 were for diabetes [23,25,26,[29][30][31][32][33][34][37][38][39]53], two for hypertension [50,51]; and one was for osteoporosis [52]. Eight trials considered multiple LTCs: three were diabetes and hypertension/cardiovascular risk [40][41][42]46]; one was diabetes and depression [43], one was for overweight patients with diabetes [44]; one was chronic pain and depression [22] two in China [32,50] and one each in Australia [31], Germany [51] and the United Kingdom [52]. Twelve trials were measured the effectiveness, impact or efficacy of SMAs compared to usual care [19,22,23,26,29,32,33,38,39,42,46,53], nine trials examined feasibility parameters [24,30,31,34,37,38,…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…IMGVs significantly reduce emergency department visits among patients with chronic pain, decrease pain medication usage, and increase patient mental and emotional well-being. 32 IMGV participants may experience a greater amount of social and emotional support than they would in individualized medical appointments and often report a greater quality of life. 33 Clinicians consistently report that group medical visit programs allow them to participate in a community of support, develop more personal relationships with their patients, and gain insight from patients with chronic conditions.…”
Section: Integrative Medical Group Visitsmentioning
confidence: 99%